Prevention and treatment of liver allograft antibody-mediated rejection and the role of the 'two-hit hypothesis'. Issue 2 (April 2016) - Kim, Peter T.W.; Demetris, Anthony J.; O'Leary, Jacqueline G.
Abstract : Purpose of review: The review outlines the diagnosis, prevention strategies, and possible treatment options for acute and chronic antibody-mediated rejection (AMR). Recent findings: Although rare, severe acute AMR (aAMR) usually occurs in patients with high mean fluorescence intensity despite serial dilutions or high-titer preformed class I donor-specific alloantibodies (DSA). The diagnosis is suspected when allograft dysfunction occurs with DSA, diffuse C4d staining, and a microvascular injury, and may be aided by the aAMR score. However, the incidence of and treatment approach to combined T-cell-mediated rejection (TCMR) with DSA present and some but not all features of AMR is yet to be determined. Chronic liver allograft AMR is characterized by low-grade chronic inflammation and progressive fibrosis with DSA, the chronic AMR (cAMR) score may facilitate diagnosis. The 'two-hit' hypothesis, whereby a coexistent insult upregulates human leukocyte antigen class II target antigens on the microvascular endothelium, may explain why suboptimal donors with lower sensitization levels might suffer from acute AMR and those with chronic complications (e.g., recurrent original disease) might be more susceptible to chronic AMR. Although treatment algorithms are needed, prevention is preferable and at a minimum includes transfusion minimization, and medication adherence. Summary: Severe acute AMR is rare but diagnosable, and there is need to determine the incidence of and optimal therapy for less severe combined AMR and TCMR. Chronic AMR is likely more common and of significant relevance to long-term allograft survival improvement. The two-hit hypothesis may help to explain the rarity of both findings and shed insight onto future prevention and treatment strategies.